A Multichannel THz Detector Using Integrated Bow-Tie Antennas - Hairui Liu; Junsheng Yu; Peter Huggard; Byron Alderman (International Journal of Antennas and Propagation)
This paper presents a kind of a multichannel THz detector using lens-based bow-tie array. A hyperhemispherical silicon lens is employed to provide a focal plane; 8 bow-tie elements are arranged on the focal plane with careful design to show a performance of broadband, high gain, well compact, and easy assembling. These characteristics of the detector are preferred for detecting weak THz signal. Measured far field shows that the radiation pattern of each element is shifted angularly, by ≈9°, which can be used for THz imaging. Tested responsivity of the detector shows a good spectral performance from 260 to 400 GHz: respective values were ≥220 V/W, and the best NEP is achieved at about 60 pW/. Besides that, the proposed antenna has advantages of simple structure, easy fabrication, and low cost.